2013
DOI: 10.1073/pnas.1314688110
|View full text |Cite
|
Sign up to set email alerts
|

Acellular pertussis vaccines protect against disease but fail to prevent infection and transmission in a nonhuman primate model

Abstract: Pertussis is a highly contagious respiratory illness caused by the bacterial pathogen Bordetella pertussis. Pertussis rates in the United States have been rising and reached a 50-y high of 42,000 cases in 2012. Although pertussis resurgence is not completely understood, we hypothesize that current acellular pertussis (aP) vaccines fail to prevent colonization and transmission. To test our hypothesis, infant baboons were vaccinated at 2, 4, and 6 mo of age with aP or whole-cell pertussis (wP) vaccines and chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
547
0
19

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(609 citation statements)
references
References 49 publications
43
547
0
19
Order By: Relevance
“…Although the basis of this is still not fully clear, resurgence of pertussis is prominent in countries using acellular pertussis (aP) vaccines. It is becoming more evident that aP vaccines do not induce long lasting protection [1] and studies in animal models have suggested that aP vaccination fails to prevent nasal colonization and transmission of B. pertussis [2]. Studies in a baboon challenge model showed that immunization with an alum-formulated aP vaccine protected animals from disease, but did not prevent nasal colonization or bacterial transmission to naïve animals; nasal colonization in these animals lasted at least as long as that in unvaccinated controls [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the basis of this is still not fully clear, resurgence of pertussis is prominent in countries using acellular pertussis (aP) vaccines. It is becoming more evident that aP vaccines do not induce long lasting protection [1] and studies in animal models have suggested that aP vaccination fails to prevent nasal colonization and transmission of B. pertussis [2]. Studies in a baboon challenge model showed that immunization with an alum-formulated aP vaccine protected animals from disease, but did not prevent nasal colonization or bacterial transmission to naïve animals; nasal colonization in these animals lasted at least as long as that in unvaccinated controls [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming more evident that aP vaccines do not induce long lasting protection [1] and studies in animal models have suggested that aP vaccination fails to prevent nasal colonization and transmission of B. pertussis [2]. Studies in a baboon challenge model showed that immunization with an alum-formulated aP vaccine protected animals from disease, but did not prevent nasal colonization or bacterial transmission to naïve animals; nasal colonization in these animals lasted at least as long as that in unvaccinated controls [2]. In contrast, baboons immunized with wP vaccine cleared the bacteria faster, whereas previously infected animals were completely protected, with no nasal colonization detected after re-challenge.…”
Section: Introductionmentioning
confidence: 99%
“…46 Furthermore, immunity induced by whole-cell vaccine also protects against mucosal infection, hence possibly limiting or interrupting transmission of Bordetella pertussis , an effect which is not observed following aP vaccination in baboon model challenge studies. 47 Nevertheless, concern regarding the reactogenicity of whole-cell pertussis vaccine, has resulted in most high-income and some low-middle income countries transitioning to aP vaccines. The increase in frequency and magnitude of current pertussis outbreaks might also be due to changes in lower threshold for investigating and the use of more sensitive molecular diagnostic tool compared to traditional culture methods.…”
Section: Maternal Pertussis Vaccinationmentioning
confidence: 99%
“…Both types of vaccines protect the individual against disease but animals vaccinated with ACV were colonized to a higher level and for longer when subsequently challenged with B. pertussis, compared to animals vaccinated with WCV. 7 Interestingly, vaccine-induced immunity, either from WCV or ACV, was inferior to immunity arising from natural infection in terms of protecting against colonisation following subsequent challenge. 7 Thus, it is very likely that the switch to the use of an ACV has changed the epidemiology of pertussis, resulting in the changing disease patterns observed.…”
Section: Resurgencementioning
confidence: 99%
“…7 Interestingly, vaccine-induced immunity, either from WCV or ACV, was inferior to immunity arising from natural infection in terms of protecting against colonisation following subsequent challenge. 7 Thus, it is very likely that the switch to the use of an ACV has changed the epidemiology of pertussis, resulting in the changing disease patterns observed.…”
Section: Resurgencementioning
confidence: 99%